2006
DOI: 10.1111/j.1537-2995.2007.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring survival and function of transfused platelets in Bernard‐Soulier syndrome by flow cytometry and a cone and plate(let) analyzer (Impact‐R)

Abstract: Transfused PLTs were detectable by flow cytometry, and their functional activity was demonstrated by the Impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…23,27 In brief, 130 mL of lithium heparin-anticoagulated whole blood were placed on the polystyrene plate. Shear stress was immediately applied (2050 s 21 ) using an acrylnitril-butadien-styrene cone.…”
Section: Impact-rmentioning
confidence: 99%
“…23,27 In brief, 130 mL of lithium heparin-anticoagulated whole blood were placed on the polystyrene plate. Shear stress was immediately applied (2050 s 21 ) using an acrylnitril-butadien-styrene cone.…”
Section: Impact-rmentioning
confidence: 99%
“…It has been shown that the enhancing effect of thrombin on the glycoprotein GPIb interaction with von Willebrand factor can be abolished by hirudin [15]. Similar to the absence of active glycoprotein GPIb in Bernard-Soulier patients [16], inhibition of the glycoprotein GPIb-thrombin binding site is likely to result in decreased platelet adherence under high shear conditions. Adhesion, however, was similar in the presence of heparin and lepirudin, and both anticoagulants inhibited thrombin-inducible platelet activation.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, only two reports described the anesthetic and perioperative management of the patient in depth [16,17]. As yet, allogeneic platelet transfusions are the only treatment with proven efficacy for BSS patients [18]. We estimated the demand for platelet units based on the monitoring of the bleeding time, resulting in the transfusion of 20 units the day before and 30 units on the date of surgery.…”
Section: Discussionmentioning
confidence: 99%